1997
DOI: 10.1006/jmbi.1996.0865
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based identification of a ricin inhibitor

Abstract: Ricin is a potent cytotoxin which has been used widely in the construction of therapeutic agents such as immunotoxins. Recently it has been used by governments and underground groups as a poison. There is interest in identifying and designing effective inhibitors of the ricin A chain (RTA). In this study computer-assisted searches indicated that pterins might bind in the RTA active site which normally recognizes a speci®c adenine base on rRNA. Kinetic assays showed that pteroic acid could inhibit RTA activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
131
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(135 citation statements)
references
References 29 publications
4
131
0
Order By: Relevance
“…Subsequent kinetic measurements confirmed that PTA was a modest inhibitor of RTA action, and the X-ray structure of the complex confirmed that the proposed mode of binding was very similar to the observed binding. 22 Pteroic acid is poorly soluble and has limited value as a lead compound for the design of effective inhibitors and useful RIP antidotes. Energy calculations were used to investigate likely binding modes of other potential inhibitors, including tautomers of pterins and guanine.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent kinetic measurements confirmed that PTA was a modest inhibitor of RTA action, and the X-ray structure of the complex confirmed that the proposed mode of binding was very similar to the observed binding. 22 Pteroic acid is poorly soluble and has limited value as a lead compound for the design of effective inhibitors and useful RIP antidotes. Energy calculations were used to investigate likely binding modes of other potential inhibitors, including tautomers of pterins and guanine.…”
Section: Introductionmentioning
confidence: 99%
“…A clear inhibition of activity for both RTA and Stx2 was observed with IC 50 values of z105 mM and z110 mM, respectively. The qRT-PCR assay showed a z6-fold decrease, from 600 mM to 100 mM, in the measured IC 50 for PTA compared to the IC 50 measurements made using in vitro translation (Yan et al 1997). We failed to see significant inhibition of RTA depurination by 9OG at any concentration <1 mM (open triangle; large dashed line), and observed only 16% inhibition of depurination at 333 mM and 35% inhibition at 1 mM.…”
Section: Inhibition Of Depurination By Small Molecule Inhibitorsmentioning
confidence: 60%
“…Pteroic acid (PTA) is an adenine analog which was shown by X-ray crystallography to bind to the active site of RTA and was kinetically shown to inhibit RTA with an IC 50 of 600 mM when assayed by in vitro translation using Artemia salina ribosomes (Yan et al 1997). 8-methyl-9-oxo-guanine (9OG) was previously reported as a more potent inhibitor than PTA in the Artemia translation system with an IC 50 of 400 mM (Miller et al 2002).…”
Section: Inhibition Of Depurination By Small Molecule Inhibitorsmentioning
confidence: 99%
“…It showed clear contacts with the key active site residue, Arg162, even at the 2.5 cutoff in the ͉2F o Ϫ F c ͉ map. Synthetic pteridine derivatives have been identified as some of the most potent inhibitors of RIPs in vitro (41)(42)(43). Some of the pteridine derivatives are also abundant in plant vacuoles and are known to inhibit the enzymes involved in the purine metabolism (44).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, synthetic inhibitors of ricin and ebulin are deeply embedded inside the cleft, mimicking the adenine base and other substrate analogs (Fig. 5B) (42,50,51). They inhibit by occupying all of the space in the active site cleft.…”
Section: Resultsmentioning
confidence: 99%